2013
DOI: 10.1021/jp4077454
|View full text |Cite
|
Sign up to set email alerts
|

Dinitrogen Release from Arylpentazole: A Picosecond Time-Resolved Infrared, Spectroelectrochemical, and DFT Computational Study

Abstract: p-(Dimethylamino)phenyl pentazole, DMAP-N5 (DMAP = Me2N-C6H4), was characterized by picosecond transient infrared spectroscopy and infrared spectroelectrochemistry. Femtosecond laser excitation at 310 or 330 nm produces the DMAP-N5 (S1) excited state, part of which returns to the ground state (τ = 82 ± 4 ps), while DMAP-N and DMAP-N3 (S0) are generated as double and single N2-loss photoproducts with η ≈ 0.14. The lifetime of DMAP-N5 (S1) is temperature and solvent dependent. [DMAP-N3](+) is produced from DMAP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 70 publications
0
24
0
Order By: Relevance
“…However, the origin of the radical anion in the experiments reporting the gas‐phase production of cyclo‐N 5 − was unclear. Attempts to reduce aryl pentazoles electrochemically or with alkali metals in solution did not lead to the detection of cyclo‐N 5 − . The proposed weakening of the C−N bond in the RA was supported by a recent theoretical study, in which it was shown that the phenylpentazole radical anion (PPRA) is stable and observable at low temperatures in polar solvents.…”
Section: Methodsmentioning
confidence: 99%
“…However, the origin of the radical anion in the experiments reporting the gas‐phase production of cyclo‐N 5 − was unclear. Attempts to reduce aryl pentazoles electrochemically or with alkali metals in solution did not lead to the detection of cyclo‐N 5 − . The proposed weakening of the C−N bond in the RA was supported by a recent theoretical study, in which it was shown that the phenylpentazole radical anion (PPRA) is stable and observable at low temperatures in polar solvents.…”
Section: Methodsmentioning
confidence: 99%
“…This conclusion is consistent with the experimental results. 25,27,[34][35][36] E a,2 s of derivatives are generally larger than that of A. Although the increases in E a,2 caused by introduction of electron donating groups are not signicant, these groups generally do improve the stability of the pentazole.…”
Section: Stability Of the Pentazole Ringmentioning
confidence: 95%
“…According to experimental investigations, [25][26][27][34][35][36]60 A and its derivatives easily decompose into N 2 and azido compounds. This suggests that breaking of the N-N bonds of the N 5 ring may take place.…”
Section: Stability Of the Pentazole Ringmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Its high-energy release and environmentally friendly products are the main reasons for many years of pursuit. 3–10 However, cyclo -N 5 − obtained from the experimentally synthesized scheme is extremely short-lived, unstable under common conditions, and extremely susceptible to decomposition into N 2 and N 3 − . 11–13 Therefore, stability has always been one of the important topics in the study of cyclo -N 5 − -containing HEDMs.…”
Section: Introductionmentioning
confidence: 99%